Recombinant β-Carotene Production by Yarrowia lipolytica – Assessing the Potential of Micro-Scale Fermentation Analysis in Cell Factory Design and Bioreaction Optimization - Jacobsen, Irene Hjorth; Ledesma-Amaro, Rodrigo; Martinez, José Luis (Frontiers in Bioengineering and Biotechnology, 2020)
The production of β-carotene has become increasingly interesting within the biotechnological industry due to a rising demand for safer and more natural colorants, nutritional supplements, and antioxidants. A recent study has described the potential of Yarrowia lipolytica as a β-carotene-producing cell factory, reporting the highest titer of recombinant β-carotene produced to date. Finding the best conditions to maximize production and scaling up the process to full scale, a costly and time-consuming process, it is often a bottleneck in biotechnology. In this work, we explored the benefits of using micro-fermentation equipment to significantly reduce the time spent on design and optimization of bioreaction conditions, especially in the early stages of process development. In this proof-of-concept study, a β-carotene producing Y. lipolytica strain was tested in micro-fermentations partly to assess the robustness of the cell factory design and partly to perform media optimization. The medium optimization led us to an improvement of up to 50% in the yield of β-carotene production in the best of the conditions. Overall, the micro-fermentation system had a high degree of reliability in all tests.